Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Lesbian sources: A bibliography of periodical articles, 1970-1990. - Garber, Linda (Garland Gay and Lesbian Studies, 2016)
Une bibliographie complète d'articles sur les lesbiennes publiés dans des périodiques diffusés à l'échelle nationale et internationale, comprenant quelque 3 500 entrées par et sur les lesbiennes. Les citations sont référencées et répertoriées de manière multiple dans plus de 100 catégories, y compris des sujets traditionnels du monde humanitaire. Il s'agit du dernier volume de neuf d'une série sur les études gays et lesbiennes. Publié initialement en 1993, Lesbian Sources est une bibliographie croisée d'articles écrits par et/ou sur des lesbiennes et publiés dans des périodiques distribués au niveau national ou international entre 1970 et 1990.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; régions géographiques; thématiques; états-unis

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences